Cinnamon Toast Crunch is always the answer
Hi there ! i think is number one. or a
I'm not sure if this is the easiest way of doing this, but it surely work.
Let the base of the triangle be AB, and let CH be the height. Just for reference, we have
![AH=2,\quad HB=6,\quad AC=x](https://tex.z-dn.net/?f=AH%3D2%2C%5Cquad%20HB%3D6%2C%5Cquad%20AC%3Dx)
Moreover, let CH=y and BC=z
Now, AHC, CHB and ABC are all right triangles. If we write the pythagorean theorem for each of them, we have the following system
![\begin{cases}4+y^2=x^2\\36+y^2=z^2\\x^2+z^2=64\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D4%2By%5E2%3Dx%5E2%5C%5C36%2By%5E2%3Dz%5E2%5C%5Cx%5E2%2Bz%5E2%3D64%5Cend%7Bcases%7D)
If we solve the first two equations for y squared, we have
![y^2=x^2-4\\y^2=z^2-36](https://tex.z-dn.net/?f=y%5E2%3Dx%5E2-4%5C%5Cy%5E2%3Dz%5E2-36)
And we can deduce
![z^2 = x^2+32](https://tex.z-dn.net/?f=z%5E2%20%3D%20x%5E2%2B32)
So that the third equation becomes
![x^2+x^2+32=64 \iff 2x^2 = 32 \iff x^2=16 \iff x=4](https://tex.z-dn.net/?f=x%5E2%2Bx%5E2%2B32%3D64%20%5Ciff%202x%5E2%20%3D%2032%20%5Ciff%20x%5E2%3D16%20%5Ciff%20x%3D4)
(we can't accept the negative root because negative lengths make no sense)
Answer:
Step-by-step explanation:
a) (a + b)² = (a + b) * (a +b)
(a + b)³ = (a + b) * (a +b) * (a +b)
a²- b² = (a +b) (a - b)
Here (a + b) is common in all the three expressions
HCF = (a + b)
b) (x - 1) = (x - 1)
x² - 1 = (x - 1) * (x + 1)
(x³ - 1) = (x - 1) (x² + x + 1)
HCF = (x -1)
Answer:
Translation 2 units downward
Step-by-step explanation:
If we start with the graph of f(x) = 3x + 8 and translate it 2 units downward, we'll end up with the graph of g(x) = 3x + 6. Note: 8 - 2 = 6.